2013
DOI: 10.1155/2013/202835
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam in Subarachnoid Block: Current Evidence

Abstract: Midazolam, despite of being the commonest benzodiazepine used in anaesthesia and perioperative care, is a relatively newer addition to the list of adjuvant used in subarachnoid block. Midazolam causes spinally mediated analgesia and the segmental analgesia produced by intrathecal midazolam is mediated by the benzodiazepine-GABA receptor complex. Initial animal studies questioned the safety of intrathecal midazolam in terms of possible neurotoxicity. However subsequent clinical studies also failed to show any n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Therefore, it can be helpful to develop a technique that allows sparing of the neuraxial opioid, replacing it with other adjuvants. This strategy was based on limited but encouraging evidences that midazolam and ketamine significantly improve the duration and quality of spinal anesthesia, reduce the onset time of sensory and motor block, provide a mild intraoperative sedative effect, ensure prolonged perioperative analgesia due to delayed recovery time of sensory block, and decrease the incidence of postoperative nausea and vomiting (PONV) without negative effects on perioperative hemodynamics, significant adverse effects, and neurotoxicity [ [29] , [30] , [31] ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it can be helpful to develop a technique that allows sparing of the neuraxial opioid, replacing it with other adjuvants. This strategy was based on limited but encouraging evidences that midazolam and ketamine significantly improve the duration and quality of spinal anesthesia, reduce the onset time of sensory and motor block, provide a mild intraoperative sedative effect, ensure prolonged perioperative analgesia due to delayed recovery time of sensory block, and decrease the incidence of postoperative nausea and vomiting (PONV) without negative effects on perioperative hemodynamics, significant adverse effects, and neurotoxicity [ [29] , [30] , [31] ].…”
Section: Discussionmentioning
confidence: 99%
“…A regimen of “opioid-free” postoperative continuous analgesia, such as that adopted in our study, which might provide similar results in pain management allowing at the same time to avoid the serious adverse effects of intrathecal opioids, can be a precious resource in older surgical patients. The potent analgesic effect of intrathecal midazolam may be induced by the release of an endogenous opioid acting at spinal δ receptors combined with its predominant agonistic action on the GABA-A receptors located in lamina II of dorsal horns of human spinal cord [ 29 ]. Minimal systemic absorption and the absence of systemic and neurological adverse effects are the other remarkable advantages of this benzodiazepine when used intrathecally compared to opioids [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Midazolam as antiemetic acts by reducing synthesis, release and postsynaptic effect of dopamine at chemoreceptor trigger zone. 14,15 There have been earlier studies for evaluating the efficacy of intrathecal midazolam in prevention of PONV. Suwalka et al 16 evaluated the postoperative analgesic effect of intrathecal midazolam-lignocaine mixture in patients undergoing caesarean section and found that incidence of nausea and vomiting was less in midazolam group when compared to lignocaine group(1:8).…”
Section: Resultsmentioning
confidence: 99%
“…It has been extensively used both in critical care medicine and operating room for its sedative, anxiolytic and amnestic effects; but probable use of intrathecal midazolam as an adjuvant to bupivacaine is a comparatively newer concept in anaesthesia practice. 3 With the discovery of benzodiazepine receptors in spinal cord in 1977, intrathecal use of midazolam for potentiating the effect of anaesthetics used in subarachnoid block was started. 4 It acts through BZD-GABA receptor complex at spinal cord level, specifically GABA-A receptors which are in highest concentration in lamina-II or the dorsal horn ganglia leading to segmental analgesia without any neurotoxic effects.…”
Section: Resultsmentioning
confidence: 99%